Requirement of ZO-1 for the formation of belt-like adherens junctions during epithelial cell polarization - Ikenouchi, Junichi (The Rockefeller University Press, 2007)
The molecular mechanisms of how primordial adherens junctions (AJs) evolve into spatially separated belt-like AJs and tight junctions (TJs) during epithelial polarization are not well understood. Previously, we reported the establishment of ZO-1/ZO-2–deficient cultured epithelial cells (1[ko]/2[kd] cells), which lacked TJs completely. In the present study, we found that the formation of belt-like AJs was significantly delayed in 1(ko)/2(kd) cells during epithelial polarization. The activation of Rac1 upon primordial AJ formation is severely impaired in 1(ko)/2(kd) cells. Our data indicate that ZO-1 plays crucial roles not only in TJ formation, but also in the conversion from “fibroblastic” AJs to belt-like “polarized epithelial” AJs through Rac1 activation. Furthermore, to examine whether ZO-1 itself mediate belt-like AJ and TJ formation, respectively, we performed a mutational analysis of ZO-1. The requirement for ZO-1 differs between belt-like AJ and TJ formation. We propose that ZO-1 is directly involved in the establishment of two distinct junctional domains, belt-like AJs and TJs, during epithelial polarization.